Effect of Lopping and Root Barrier on Pasture Production in Colophospermum mopane Based Silvipastoral System in Western Rajasthan - Singh, Bilas; Bishnoi, Mahipal; Singh, G. (International Journal of Bio-resource and Stress Management, 2017)
Economy of the people of dry region mainly depends on animal husbandry, where silvopastoral system plays an important role by providing not only grass fodder but also feed from the tree component together with benefits of carbon sequestration and soil improvement. Tree component influences pasture production by competing for light, soil water and nutrients, which needs to be managed for increased production. A silvopastoral experiment was conducted at AFRI, Jodhpur involving Cenchrus ciliaris grassintercropped with17 years old Colophospermum mopane treesat spacing of 5×10 m2. Four treatments were: Intact tree, Tree pruning up to 70% tree height, root barrier treatment, and both tree pruning and root barrier treatment. Pooled data of last four years revealed non-significant variations in clump number, tillers number and clump diameter of C. ciliaris grass among treatments and sole grass plots. Dry mass production of C. ciliaris was significantly high in sole grass plot than in treatments. However, grass production was highest in pruned and root barrier tree and lowest in intact tree than in other treatments. Photosnthetically Active Radiation (PAR) was highest (p<0.05) in sole grass plots. PAR varied from 325 to 1285 µmol m-2 s-1. PAR was highest in lopped and root barrier tree and increased with distances from tree trunk. Soil water content (SWC) increased (p<0.05) with increasing soil depth and distances from tree. SWC was highest in pruned and root barrier tree than intact tree. Results indicate that tree pruned along with root barrier is beneficial in enhancing productivity of silvipostoral system in dry areas